Asset Insurance Under Rising Disasters: Financial Value and Simulation Evidence - Kusdaryanto, Pranidhana Putra (Jurnal Manajemen dan Inovasi (MANOVA), 2026)
Objective – This paper evaluates whether insuring public assets is financially beneficial under increasing disaster risk, with emphasis on the trade-off between expected cost and tail-risk protection relevant to public asset management. Design/methodology/approach – The study integrates disaster-risk financing and insurance-demand theory with a Monte Carlo simulation of a representative public-asset portfolio over a 10-year horizon. The simulation models increasing hazard frequency, skewed loss severity, inflation, and a simplified insurance contract (deductible and limit). Outcomes are assessed using expected net present value (NPV) of total cost, downside risk (P95/P99), and the probability of breaching a fiscal-stress threshold. Findings – Insurance increases expected NPV cost under plausible premium loadings, yet it materially reduces tail risk. In the base case, the P95 of total cost falls from 182.0 to 96.6 IDR bn, and the probability of NPV exceeding IDR 200 bn drops from 3.9% to 0.6%. Therefore, insurance can be financially rational when decision-makers value budget stability and service-continuity protection more than expected-cost minimisation. Research limitations/implications – Quantitative outputs are illustrative because parameters are not calibrated to a specific ministry asset register, peril mix, and vulnerability. Future work should calibrate catastrophe models to BMN portfolios and incorporate premium dynamics under hardening reinsurance markets. Practical implications – The framework supports risk appetite setting, deductible/limit optimisation, and integration of insurance with maintenance, retrofit, and contingency reserves. Originality/value – The paper bridges public asset management and disaster-risk financing by translating insurance decisions into NPV and tail-risk metrics that are actionable for portfolio governance.